Lumberjanes. Volume ten, Parents' day - Watters, Shannon; Leyh, Kat (Boom! Box, 2018)
When the Lumberjanes' parents come to the camp for Parents' Day, the girls have to prevent their parents from learning about the supernatural things happening in the woods. But that could be more complicated than it sounds when mysterious forces are at play.